Nongenetic pathologic developments of brain-wave patterns in monozygotic twins discordant and concordant for schizophrenia - Weisbrod, Matthias; Hill, Holger; Sauer, H.; Niethammer, Rainer; Guggenbühl, S.; Hell, D.; Stassen, H. H. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2004)
Evidence from previous studies has suggested that the inter-individual differences in human brain-wave patterns (EEG) are predominantly determined by genetic factors. In particular, the within-pair EEG concordance of monozygotic (mz) twins was found to be typically as high as r = 0.81 across channels and frequency bands, thus being comparable to that between repeated assessments on the same individual with typically r = 0.83. Yet our investigations into mz twins discordant and concordant for schizophrenia yielded a significantly reduced within-pair EEG concordance for both, the pairs discordant for schizophrenia and the pairs concordant for schizophrenia (with concordance for schizophrenia assessed through a syndrome-oriented approach). A multivariate discriminant function of EEG parameters distinguished in a reproducible way between affected and unaffected subjects at an overall performance of >75% correctly classified subjects, while the severity of illness, as derived from EEG-differences between affected and unaffected subjects, was closely related to the severity of illness as provided by psychopathology syndrome scores. Consequently, EEG anomalies associated with schizophrenia and manifested differently in the mz co-twins concordant for schizophrenia are likely the effect of nongenetic, pathologic processes that evolved independently in the co-twins' genetically identical brains once the illness began to progress. The existence of such nongenetic processes would suggest a modification of the standard phenotype-to-genotype search strategies of molecular-genetic studies that aim to link the schizophrenia phenotype to genetic vulnerability factors. © 2003 Wiley-Liss, Inc.
First published: 25 August 2003
Gesehen am 22.12.2021